Synthetic approaches for novel fused pyrimidine derivatives: Design, structural characterization, antiviral, antitumor, and molecular docking evaluation - Fatmah O. Sefrji; Abdulmajeed F. Alrefaei; Mohammed A. Imam; Gadeer R.S. Ashour; Matokah M. Abualnaja; Roba M.S. Attar; A.A.A. Darwish; Nashwa M. El-Metwaly (Heliyon)
The goal of this work was to synthesize new compounds for anticancer evaluation as a trial to obtain new antitumor agents with higher activity and fewer side effects. Therefore, the precursor 2,2'-(1,4-phenylenebis (thiazole-4,2-diyl))bis (3-(dimethylamino)acrylonitrile) (4) was used to synthesize various azolopyrimidine derivatives connected to the thiazole moiety. Compounds 5–11, including pyrazolopyrimidine, triazolopyrimidine, and others, were produced by reacting enaminonitrile 4 with different N-nucleophiles. Additionally, compounds 12–15, such as isoxazole and pyrimidinethione derivatives, were obtained by reacting compound 4 with guanidine, hydrazine hydrate, hydroxylamine hydrochloride, and thiourea. Enaminonitrile 4 was also treated with barbituric acid, isoxazolone, and pyrazolone to yield pyranopyrimidine derivatives 18–20. Moreover, enaminonitrile 4 reacts with C-nucleophiles namely ''acetylacetone, dimedone, 2-cyanomethylbenzothiazole, and 2-cyanomethylbenzimidazole'' to give pyrano derivatives 21, 22 and fused pyridone derivatives 23 and 24, respectively. The cytotoxic activity of 20 novel compounds against HSV-1, HIV-1, and various cancer cell lines was assessed, with compounds 5, 7, and 9 showing the strongest effects. Molecular docking studies further evaluated the binding affinity of these derivatives, with docking scores ranging from −7.8679 to −8.3013 kcal/mol. Several new azolopyrimidine derivatives linked to the thiazole moiety were effectively synthesized and assessed in the study, and they showed notable cytotoxic activity against HSV-1, HIV-1, and several cancer cell lines.